2013
DOI: 10.1002/cmdc.201200516
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Marine Triterpene Sipholenols as Inhibitors of Breast Cancer Migration and Invasion

Abstract: Sipholenol A, a sipholane triterpene isolated from the Red Sea sponge Callyspongia siphonella, has the ability to reverse multidrug resistance in cancer cells that overexpress P-glycoprotein (P-gp). Here, the antimigratory activity of sipholenol A and analogues are reported against the highly metastatic human breast cancer cell line MDA-MB-231 in a wound-healing assay. Sipholenol A and sipholenone A were semisynthetically optimized using ligand-based strategies to generate structurally diverse analogues in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 67 publications
(67 reference statements)
0
29
0
Order By: Relevance
“…Ester analogs of 1 were more active than ether, oxime and carbamate analogs. This illustrates the important role of the ester carbonyl group as well as the distance limit between the aromatic side chain and C-4 oxygen for optimal antimigratory activity [49]. Longer distances, as represented by oximes or carbamates, significantly decreased the antimigratory activity.…”
Section: Sipholanes As Novel Inhibitors Of Migration Proliferation Amentioning
confidence: 96%
See 3 more Smart Citations
“…Ester analogs of 1 were more active than ether, oxime and carbamate analogs. This illustrates the important role of the ester carbonyl group as well as the distance limit between the aromatic side chain and C-4 oxygen for optimal antimigratory activity [49]. Longer distances, as represented by oximes or carbamates, significantly decreased the antimigratory activity.…”
Section: Sipholanes As Novel Inhibitors Of Migration Proliferation Amentioning
confidence: 96%
“…Aromatic esters showed a better activity profile than aliphatic esters; for example, the benzoate 28 was twice as active as the acetate 25 (Table 26.2). The aromatic ester was tolerant to bioisosteric substitution as evident from the comparable activity of isonicotinate ester (29) to the benzoate ester 28 (Table 26.2) [49]. In order to identify a potential target, KINOME scan profiling was performed to quantitatively measure interactions between the most active ester analog 34 and a diverse kinase panel [49].…”
Section: Sipholanes As Novel Inhibitors Of Migration Proliferation Amentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the antimigratory activity of sipholenol A and analogues was reported against the highly metastatic human breast cancer cell line MDA-MB-231 in a wound-healing assay. 48 Neviotine-A (133) possessing a unique tetracyclic skeleton related to the sipholanes and siphonellanes, was isolated from the Red Sea sponge Siphonochalina siphonella. Its structure was elucidated mainly on the basis of NMR experiments and by chemical transformations and.…”
Section: Triterpenesmentioning
confidence: 99%